Nature as God: A juxtaposition of Vito Mancuso and Alexander von Humboldt in their search for understanding reality - Buitendag, Johan (HTS teologiese studies, 2021)
This article’s premise is that science holds the promise of deepening religious perspectives on creation. The natural sciences have convincingly proved that nature is not static, or a ready-made creation dropped from heaven. Theologians need to read nature as scientists see it and engage with that understanding theologically.The concept of resonance is applied to denote this tangential relationship as an eco-social constructivist understanding of reality. Two proponents, one scientist and one theologian, have been chosen who share this view of a holistic reality, and the objective is to determine the degree of resonance viable of these magisteria. A method of polycentric hermeneutics is thus pursued.Although we referred to the concept of consilience regarding von Humboldt’s enterprise, it is not in the authors’ scope to achieve this with science and theology as disciplines sui generis. However, if resonance becomes vital in understanding reality, faith is inevitable (Anselm). If a creation theology seeks a degree of plausibility, it requires the feedback-loop methodology of science. We all share one earth: the closer we all come to a shared end, the closer we also come together and relativise differences. The naturalist Edward O. Wilson suggested that science and religion should set aside their differences to save the planet. Resonance has the potential to let new horizons emerge in our mutual endeavour to come to grips with reality and to map out certain tangentially overlapping magisteria.Contribution: Through resonance, the thought constructs of a scientist and a theologian are juxtaposed. An iterative hermeneutics’ importance is emphasised in the theology and science discourse, if faith seeks understanding and leads to awe. And the conclusion is that the ‘spiritual dimension’ and the ‘natural dimension’ do not only overlap but are tangential, as they engage with the same reality.